Optimalisasi Literasi Digital dan Etika Bermedia Sosial Melalui Edukasi Partisipatif di SMK Muhammadiyah 9 Jakarta - Alessandro Kurniawan Ulung; Fahlesa Munabari; Riena F. Telussa; Andina M. Ayu; Christina Christina; Natrion Natrion; Abdul Kholiq; Pradono B. Saputro; Ariel Juan Sinaga (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This Community Service Program (PKM) aims to enhance digital literacy and social media ethics among students at SMK Muhammadiyah 9 Jakarta. The program was implemented by a team of lecturers from Universitas Satya Negara Indonesia (USNI), using a participatory education approach integrated with experiential learning. The activities included educational sessions, interactive discussions, case-based simulations, and hands-on practice in creating educational digital content, encouraging students' active engagement throughout the learning process. The evaluation results showed that the program increased 40 students' digital literacy by 46% and their understanding of social media ethics by 53%. These improvements were evidenced by comparisons of the pre-test and post-test results, as well as by the students' ability to produce educational digital content as a practical application of the knowledge they had acquired. The findings indicate that the participatory education approach was effective not only in improving students' knowledge but also in developing practical skills, critical thinking, and more responsible, ethical, and informed attitudes toward the use of digital media. Therefore, the learning model implemented in this community service program has the potential to be replicated in other schools as an effective strategy for strengthening digital literacy and fostering a healthy and responsible digital culture within educational settings.